DETERMINANTS OF OUTWARD FOREIGN DIRECT INVESTMENT FROM EMERGING MARKETS: THE CASE OF THAILAND - Dao, Linh (2018)
Foreign direct investment (FDI) has increasingly played a major role in today international business as a dynamic driver for economic growth. Firms from emerging markets, despite of lacking traditional firm-specific advantages, have become significant sources of outflow investment. Their investment has not only flow into developing countries but also developed countries, where firms possess strong ownership assets. In recent year, the outflow of investment from Asia has been recorded with impressive growth. Going from a small player with only 7 percent of global outward investment in 2005, outflow from this region has become a major driver as it accounted for 16 percent of the world’s total outflows in 2012. This interesting trend, therefore, has attracted many studies in recent years. However, while there are a huge number of researches on the outflow FDI from China, other emerging markets have been given little attention. This dissertation, therefore, will concentrate on filling that gap with investigation of the factors that influence the outflow investments of firms from Thailand. Recent years, among the four new Asian tigers, only the outflows from Thailand has witness an increasing trend. Using quantitative methodology on the database of 17 developing and developed countries in 12 years from 2005-2016, this dissertation examines the determinants of investment outflow from Thailand. The findings from this study, after testing a number of hypotheses based on Eclectic paradigm and Institutional theory, provides interesting implications of outward FDI from Thailand. While the motivation of Thai firms to invest into developed and developing although share some factors in common, abundance of labour was found significant only for outflow to developing countries while strategic asset-seeking motive is only applied for outflow into developed economies. Moreover, while the Institutional theory has strong explanation capacity for developing countries, it has limited impact on outward FDI to developed economies.